Product-Service System Implementation for Competitive Advantage in International Freight Forwarding: A Case Study of PT Choir Express - Ecklesia Anastasya Pinem (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This research examines Product-Service System (PSS) implementation as a strategic framework to enhance competitiveness in the international freight forwarding industry, specifically analyzing PT Choir Express's transformation opportunities from pure service provision toward integrated product-service offerings. Methodology: The study employs Tukker's (2004) PSS classification framework through questionnaire-based organizational capability assessment, evaluating PT Choir Express across eight PSS categories spanning Product-Oriented, Use-Oriented, and Result-Oriented service dimensions. Results: PT Choir Express currently operates in Quadrant 11 (Pure Service), with eligibility for seven PSS quadrants including Product Related Service, Advice & Consulting, Product Related Software, Product Pooling, Outsourcing, Pay Per Service Unit, and Functional Result. Findings: The company possesses critical capabilities including specialized human resources, software infrastructure, and partnership networks, but faces financial resource constraints limiting comprehensive PSS transformation. Novelty: This research extends PSS theory beyond product-oriented manufacturing to service-dominant logistics, demonstrating novel adoption pathways for freight forwarding companies in emerging markets. Conclusion: A phased PSS implementation strategy prioritizing lower-investment Product-Oriented services before progressing to Result-Oriented offerings enables competitive differentiation and sustainable growth despite financial constraints. Type of Paper: This paper is an empirical research paper.